Sleep-Promoting Effects and Possible Mechanisms of Action Associated with a Standardized Rice Bran Supplement - Yang, Hyejin (Nutrients, 2017)
Natural sleep aids are becoming more popular due to the widespread occurrence of sleep disorders. The objective of this study was to assess the sleep-promoting effects of rice bran—a product that is considered as a functional ingredient. To evaluate the sleep-promoting effects of a standardized rice bran supplement (RBS), we employed a pentobarbital-induced sleep test and conducted analyses of sleep architecture. In addition, the effect of RBS on a caffeine-induced sleep disturbance was investigated. Oral administration of RBS (500 and 1000 mg/kg) produced a significant decrease in sleep latency and increase in sleep duration in pentobarbital-induced sleep in mice. Moreover, both RBS (1000 mg/kg) and doxepin hydrochloride (histamine H(1) receptor antagonist, 30 mg/kg) counteracted a caffeine-induced sleep disturbance in mice. In terms of sleep phases, RBS (500 mg/kg) promoted non-rapid eye movement sleep for the first 3 h following its administration. Lastly, we unveiled a possible mechanism for RBS action as the hypnotic effect of RBS was blocked by a histamine H(1) receptor agonist. The present study revealed sleep-promoting effects of RBS using various animal assays. Such effects seem to be mediated through the histaminergic system. Our findings suggest that RBS may be a promising natural aid for relieving sleep problems.